Application of Good Governance Principles in Government: Perspective of Public Services - Heru Rochmansjah (GoAcademica Research & Publishing, 2019)
The community has waited a long time and hopes for the government to implement good governance, namely effective, efficient, accountable, and responsible governance. However, until now, there has not been a comprehensive and systematic strategy in realizing good governance, which is likely due to the broad scope of good governance dimensions and the lack of priority scale due to population diversity and the unavailability of adequate information. So for the initial step, researchers suggest that improving the implementation of public services is the first step in bureaucratic development reform.